Harga diri (self esteem) lansia yang mengalami demensia - Ganda Sigalingging; Zulkarnain Nasution; Rustina Pasaribu (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Self esteem in elderly persons with dementiaBackground : The triple threat is a challenge that must be faced in Indonesia. More and more the number of elderly that continues to increase. As you age, changes occur due to the aging process that causes physical and psychosocial problems. one of the psychosocial problems in the elderly is low self-esteem. If that doesn't work, the elderly will repair, attract, challenge, and even escape.Purpose :To analyze the relationship between dementia and self-esteem (self-esteem) in the elderly at the Guna Budi Bakti Foundation in Medan.Method: This analytical survey research cross sectional approach. Seventy two elderlywere involved as the population in this research.This research used total sampling technique where in the number of sample equals to the number of population. In analyzing the data, chi-square test was used.Results: Shows that older people reduce moderate dementia 44.4% with a low self-esteem 69.4%. With the statistical test results there was a relationship dementia and self-esteem in the elderly, with p-value of 0.003 Conclusion: There was a relationship dementia with of self-esteem for elderly in Panti Jompo Guna Budi Bakti Foundation in MedanKeywords: Dementia; Self-esteem; ElderlyPendahuluan: Ancaman triple burden merupakan tantangan yang harus dihadapi di Indonesia. Ancaman tersebut diantaranya jumlah lansia yang terus meningkat. Seiring pertambahan usia, terjadi perubahan sebagai akibat proses menua yang berpotensi menimbulkan masalah fisik dan psikososial. Salah satu masalah psikososial pada lansia yaitu harga diri rendah. jika tidak ditangani maka lansia mengalami depresi, menarik diri, perilaku kekerasan bahkan bunuh diri.Tujuan : Untuk menganalisa hubungan demensia dengan harga diri (self esteem) lansia di Yayasan Guna Budi Bakti Medan.Metode: Jenis penelitian survei analitik dengan pendekatan cross sectional. Populasi seluruh lansia sebanyak 72 orang dengan teknik sampel total sampling. Pengumpulan data dilakukan dengan wawancara menggunakan kuesioner. Analsisi data menggunakan uji chi- Sguare pada taraf kepercayaan 95%.Hasil: Menunjukkan lansia lebih banyak mengalami demensia sedang, sebanyak 32 orang (44,4%). dengan menunjukkan harga diri rendah sebanyak 50 orang (69,4%). Hasil uji statistik menunjukkan ada hubungan demensia dengan harga diri (self estem) lansia, dengan nilai p value = 0,003 (a < 0,05)Simpulan: Ada hubungan demensia dengan harga diri (self esteem) lansia di Panti Jompo Yayasan Guna Budi Bakti Medan.